PENERAPAN PEMBELAJARAN BERBASIS GAME WORDWALL GUNA MENINGKATKAN KOGNITIF ANAK TK B USIA 5-6 TAHUN - Putri Sholehati; Asri Widiatsih; Ahmad Afandi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study examines how Wordwall game-based evaluation improves cognitive development in 5–6-year-olds in TK B at TK Al Hikmah Puger. The study highlights the lack of engaging and interactive learning approaches in early childhood education, which hinders cognitive progress. We'll explain how Wordwall works as an assessment tool in daily learning. Qualitative descriptive data were collected from students and teachers through observation, interviews, and recording. The results show that Wordwall games improve children's memory, problem-solving, and active engagement. The results imply that game-based evaluation makes learning more fun and effective, encouraging children to participate. In conclusion, this study proposes game-based learning assessments like Wordwall in early childhood education to encourage cognitive growth and help teachers create creative and dynamic learning experiences.